A National Cohort Study Evaluating the Association Between Short-term Outcomes and Long-term Survival After Esophageal and Gastric Cancer Surgery. Issue 5 (November 2019) - van der Werf, Leonie R.; Wijnhoven, Bas P. L.; Fransen, Laura F. C.; van Sandick, Johanna W.; Nieuwenhuijzen, Grard A. P.; Busweiler, Linde A. D.; van Hillegersberg, Richard; Wouters, Michel W. J. M.; Luyer, Misha D. P.; van Berge Henegouwen, Mark I.
Abstract : Objective: The aim of this study was to investigate the association between short-term outcome indicators and long-term survival after esophagogastric resections. Summary Background Data: Short-term outcome indicators are often used to compare performance between care providers. Some short-term outcome indicators concern the direct quality of care, that is, complications, others are used because they are expected to be associated with long-term outcomes. Method: For this national cohort study, all patients who underwent esophagectomy or gastrectomy for cancer with curative intent between 2011 and 2016 and were registered in the Dutch Upper gastrointestinal Cancer Audit were included. Primary outcome was conditional survival (under the condition of surviving the first postoperative 30 days and hospital admission). Cox regression modeling was used to study the independent association between "textbook outcome" with survival. "Textbook outcome, " a composite quality indicator, was defined as a pathological complete resection with at least 15 retrieved lymph nodes, an uneventful postoperative course, and no hospital readmission. Results: In total, 4414 and 2943 patients with esophageal or gastric cancer, respectively, were included. The 1-, 2-, and 3-year overall survival rates were 76%, 62%, and 54%, and 71%, 56%, and 49% for esophageal and gastric cancer, respectively. Textbook outcome was achieved in 33% and 35% of patients respectively. "Textbook outcome" was independently associated with longer conditional survival [hazard ratio: 0.75 (95% confidence interval, 0.68–0.84) and 0.69 (0.60–0.79), respectively]. Conclusion: This study showed that the short-term outcome indicator textbook outcome is associated with long-term overall survival and therefore may accentuate the importance of using these indicators in clinical audits. Abstract : Supplemental Digital Content is available in the text